Respuesta :

Answer:

x = - 1, y = 2, z = 1

Step-by-step explanation:

Given the 3 equations

2x - y + 3z = - 1 → (1)

x + 2y - 4z = - 1 → (2)

y - 2z = 0 → (3)

Add (1) and (3) term by term

2x + z = - 1 → (4)

Multiply (1) by 2

4x - 2y + 6z = - 2 → (5)

Add (2) and (5) term by term

5x + 2z = - 3 → (6)

Multiply (4) by - 2

- 4x - 2z = 2 → (7)

Add (6) and (7) term by term

x = - 1

Substitute x = - 1 into (4)

- 2 + z = - 1 ( add 2 to both sides )

z = 1

Substitute x = - 1, z = 1 into (2)

- 1 + 2y - 4 = - 1

- 5 + 2y = - 1 ( add 5 to both sides )

2y = 4 ( divide both sides by 2 )

y = 2

solution is (x, y, z ) = (- 1, 2, 1 )